A Review On The Binder Used To Remediate The Contaminated Soil By Stabilisation Method - Mohammd Azmi, Mohamad Azim; Hamid, Noor Baizura; Mokhtar, Mardiha; Abdullah, Noorul Hudai; Shahidan, Shahiron; Ahmad Tajudin, Saiful Azhar (Multidisciplinary Applied Research and Innovation, 2021)
Soil is the essential for life, in the sense that they provide the medium for plant growth, habitat for many insects and other organisms, act as a filtration system for surface water, carbon store and maintenance of atmospheric gases. Unfortunately, soil is extremely exposable to contamination. It is necessity to treat the contaminated soils to reduce the heavy metal component in the soils. Thus, a review of the binder used to remediate the contaminated soil using the stabilization of contaminated soil with cement and waste material is chosen as it is widely applied method to sustain the environment. The method that were used is Stabilisation/Solidification (S/S) treatment process which consists addition of binders to strengthen back the soil to its formal state. It is shown by these studies that that S/S remediation methods using various type of binders has made an attempt to solve this long overdue problem. These studies found that by using recycle material or waste material such as bagasse ash, rice husk, sea-shell, and biochar able to improve the quality of soil treatment.